The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/2016gl070049
|View full text |Cite
|
Sign up to set email alerts
|

Overestimating climate warming‐induced methane gas escape from the seafloor by neglecting multiphase flow dynamics

Abstract: Continental margins host large quantities of methane stored partly as hydrates in sediments. Release of methane through hydrate dissociation is implicated as a possible feedback mechanism to climate change. Large‐scale estimates of future warming‐induced methane release are commonly based on a hydrate stability approach that omits dynamic processes. Here we use the multiphase flow model TOUGH + hydrate (T + H) to quantitatively investigate how dynamic processes affect dissociation rates and methane release. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…This builds upon previous work using T + H where Stranne et al [2016b] investigated seafloor warming-induced hydrate dissociation and found that with a seafloor warming of 3°C over 100 years, they could only accurately simulate hydrate-bearing marine sediments with permeabilities higher than 10 À15 m 2 . Hydraulic fracture dominated fluid flow appears in sediments with k ≤ 10 À16 m 2 .…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…This builds upon previous work using T + H where Stranne et al [2016b] investigated seafloor warming-induced hydrate dissociation and found that with a seafloor warming of 3°C over 100 years, they could only accurately simulate hydrate-bearing marine sediments with permeabilities higher than 10 À15 m 2 . Hydraulic fracture dominated fluid flow appears in sediments with k ≤ 10 À16 m 2 .…”
Section: Discussionmentioning
confidence: 63%
“…This means that the pore pressure at the dissociation front remains significantly lower in the base case (compare Figures 2a-2f with Figures 2g-2l) which allows for faster dissociation (as discussed at length in Stranne et al [2016b]). In the base case, pore pressure rises to just above a critical pressure (corresponding to λ Ã T ) at which point a hydraulic fracture forms.…”
Section: 1002/2017gl074349mentioning
confidence: 83%
See 3 more Smart Citations